Enhancing pre-service teachers’ science teaching efficacy beliefs and attitudes toward science using the flipped classroom model - Ribeirinha, Teresa; Correia, Marisa (Frontiers in Education, 2025)
IntroductionScience teacher education programs play a crucial role in shaping future educators. Pre-service Teachers’ (PSTs) attitudes toward science and their self-efficacy beliefs are pivotal in determining the extent to which they engage with and benefit from their academic training. The Flipped Classroom Model (FCM) offers a technology-enhanced, student-centered approach with the potential to enhance PSTs’ self-efficacy beliefs and attitudes.MethodsThis study explores the effect of an FCM approach in a general science course on the PSTs science teaching self-efficacy beliefs and attitudes toward science. The study used a mixed methods approach with 39 PSTs. The quantitative dimension adopted a semi-experimental design with a pretest-posttest control group, and qualitative data were collected through semi-structured interviews.ResultsResults suggest that the FCM had a significant effect on PSTs’ science teaching self-efficacy beliefs, particularly in the personal science teaching efficacy, and on their attitudes toward science, particularly in their perceptions of the science teacher. The themes of supportive environment and hands-on activities emerged from the qualitative analysis.DiscussionThe implementation features of the FCM, combined with teacher support, appeared to foster a more productive classroom environment that had mobilized multiple sources of self-efficacy. This environment stimulated PSTs’ interest in science and increased their confidence, thereby cultivating a greater sense of investment in their science learning. Incorporating the FCM into teacher education programs offers significant advantages in PSTs’ academic training.